Penyelesaian Sengketa Harta Bersama: Analisis Perkara Nomor: 283/Pdt.G/2017/PA.Mtr dan Nomor: 59/Pdt.G/2023/PTA.Mtr - Wati, Salma; Zulfan, Zulfan; Elfia, Elfia (Zaaken: Journal of Civil and Business Law, 2024)
One of the factors that husband and wife often dispute is regarding propertya especially joint property. Generally, disputes regarding joint property arise after a couple decides to divorce. In this situation, each party will try to get what they consider to be their right. The judiciary plays an important role in resolving these disputes. The judiciary functions as a medium for disputing husband and wife to convey their arguments, especially in efforts to control joint property. In this research the author used a normative approach method, known as the literature study method. In this research, the primary data comes from case decisions number: 283/Pdt.G/2017/PA.Mtr and number: 59/Pdt.G/2023/PTA.Mtr. then secondary data was obtained from various books, journals and articles related to the research subject. This research describes how judges consider when deciding joint property cases in cases number: 283/Pdt.G/2017/PA.Mtr and number: 59/Pdt.G/2023/PTA.Mtr. The results of this research, the author found that dispute resolution carried out by judges is not only focused on the law, but must also consider a sense of justice. So that judges do not have to divide joint assets equally but rather adhere to the principles of balance, equality, non-discrimination and granting rights to parties that are considered fair, accompanied by considerations that are considered fair. This is reflected in the decision in case number: 283/Pdt.G/2017/PA.Mtr and number: 59/Pdt.G/2023/PTA.Mtr